(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the historical, socio-cultural conditions and social environment in the Muslim East, the scientific and methodological bases of studying the interpretation of justice in the moral views of Abu Abdullah Rudaki. Also, the life and career path of Abu Abdullah Rudaki, the factors that influenced the formation of his moral views were analyzed.